Desalination Using the Capacitive Deionization Technology with Graphite/AC Electrodes: Effect of the Flow Rate and Electrode Thickness - Martinez, Jhonatan (2022)
Capacitive deionization (CDI) is an emerging water desalination technology whose principle lies in ion electrosorption at the surface of a pair of electrically charged electrodes. The aim of this study was to obtain the best performance of a CDI cell made of activated carbon as the active material for water desalination. In this work, electrodes of different active layer thicknesses were fabricated from a slurry of activated carbon deposited on graphite sheets. The as-prepared electrodes were characterized by cyclic voltammetry, and their physical properties were also studied using SEM and DRX. A CDI cell was fabricated with nine pairs of electrodes with the highest specific capacitance. The effect of the flow rate on the electrochemical performance of the CDI cell operating in charge–discharge electrochemical cycling was analyzed. We obtained a specific absorption capacity (SAC) of 10.2 mg/g and a specific energetic consumption (SEC) of 217.8 Wh/m3 at a flow rate of 55 mL/min. These results were contrasted with those available in the literature; in addition, other parameters such as Neff and SAR, which are necessary for the characterization and optimal operating conditions of the CDI cell, were analyzed. The findings from this study lay the groundwork for future research and increase the existing knowledge on CDI based on activated carbon electrodes.